Strong-coupling charge density wave in monolayer TiSe2. (12th October 2020) - Watson, Matthew D; Rajan, Akhil; Antonelli, Tommaso; Underwood, Kaycee; Marković, Igor; Mazzola, Federico; Clark, Oliver J; Siemann, Gesa-Roxanne; Biswas, Deepnarayan; Hunter, Andrew; Jandura, Sven; Reichstetter, Janika; et al.
Abstract: We study the 2 × 2 charge density wave (CDW) in epitaxially-grown monolayer TiSe2 . Our temperature-dependent angle-resolved photoemission spectroscopy measurements indicate a strong-coupling instability, but reveal how not all states couple equally to the symmetry-breaking distortion, with an electron pocket persisting to low temperature as a non-bonding state. We further show how the CDW order can be suppressed by a modest doping of around 0.06(2) electrons per Ti. Our results provide an opportunity for quantitative comparison with a realistic tight-binding model, which emphasises a crucial role of structural aspects of the phase transition in understanding the hybridisation in the ground state. Together, our work provides a comprehensive understanding of the phenomenology of the CDW in TiSe2 in the 2D limit.